Randomized Controlled Trial: Prophylactic Autologous Fascia Sling for Women at Risk of Urethral Incontinence after Obstetric Fistula Repair - Pope, Rachel; Browning, Andrew; Chipungu, Ennet; George, Jeredine; Mariatu, Tammimu; Wilkinson, Jeffrey (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To compare sling types as anti-incontinence procedure for women with obstetric fistulas at high-risk for residual incontinence. Methods: This is a multiple-site randomized controlled trial comparing autologous fascia slings to pubococcygeal (PC) slings at time of fistula repair. Participants with a Goh type 3 or 4 vesico-vaginal fistula (urethral length <2.5 cm) with no prior repair were randomized to receive either a rectus fascia sling or a PC sling while undergoing fistula repair. Interviews were performed before surgery and at follow up including the Michigan incontinence symptom index (M-ISI) and the Incontinence quality of life tool (I-QOL). Safety analysis was performed after ten participants have been enrolled in each arm. Results: Eleven participants randomized to a PC sling and ten to a rectus sling. There was one repair breakdown in the PC group and three in the rectus group. Pad weights trended lower in the rectus group. QOL and MISI scores improved significantly for both groups. The study was terminated at safety analysis due to the number of breakdowns and difficulty of follow-up at one site. Conclusions: There was no superiority between slings. Randomization proved problematic given the vast heterogeneity between fistula injuries. When compared to slings placed after an initial VVF repair in the literature, continence rate with the prophylactic rectus fascia sling was improved. There is a need for an innovative prophylactic anti-incontinence technique that does not result in repair failure.